EFEKTIVITAS PENGGUNAAN MEDIA KABOTA TERHADAP PEMAHAMAN MATEMATIS SISWA KELAS IV PADA MATERI PECAHAN - Octavia, Hanifah; Maulana, M.; Karlina, Dety Amelia (Jurnal Pena Ilmiah, 2017)
This study aims to determine the improvement of students' mathematical comprehension skills by using kabota media, the improvement of students' mathematical understanding with conventional learning and the differences of improvement between learning with kabota media and conventional approach on fractional lesson. The population of this research is all fourth grade students in Kecamatan Palasah of Majalengka Regency and the sample of this research is the students of class IV-A and IV-B at SDN Palasah I. Class IV-A is used as the experiment class that learnt using the kabota media and class IV- B is used as a control class that learnt with conventional approach. The results showed that both experimental and control classes have improved on the students' mathematical understanding on fractional lesson. This means there is not any differences in the improvement between the post-test score in the experimental class and the control class. So it can be concluded, learning using kabota media is as well as conventional approach in improving students' mathematical understanding of the fourth grade on fractional lesson.